DETERMINANTS OF TRANSFER PRICING FROM NON CYCLICAL'S AND INDUSTRIAL PERSPECTIVES - Lestari, Alicia; Bwarleling, Theresia Hesti (APPS Publications, 2024)
The aims examine the effect of bonus mechanism, effective tax rate, and debt covenant on transfer pricing in consumer non cyclicals and industrial sector companies on the Indonesia Stock Exchange in 2020-2022. The sample in this study used purposive sampling method and obtained 16 companies listed in 2020-2022 period. The analysis method used in quantitative method with multiple linear regression analysis and using SPSS 26 software. This study uses secondary data in the form of financial report obtained from www.idx.co.id. The result of multiple linear regression is that the variable of bonus mechanism and effective tax rate has no significant effect on transfer pricing, while debt covenant has positive and significant effect on transfer pricing. The variable of bonus mechanism and effective tax rate have not been proven to give significant influence. For this reason, it is expected that future research can provide result and use more appropriate proxies for each independent variable in this study.